Brome Mosaic Virus RNA Syntheses In Vitro and in Barley Protoplasts - Sivakumaran, K. (American Society for Microbiology, 2003)
The RNA replicase extracted from Brome mosaic virus (BMV)-infected plants has been used to characterize the cis-acting elements for RNA synthesis and the mechanism of RNA synthesis. Minus-strand RNA synthesis in vitro requires a structure named stem-loop C (SLC) that contains a clamped adenine motif. In vitro, there are several specific requirements for SLC recognition. We examined whether these requirements also apply to BMV replication in barley protoplasts. BMV RNA3s with mutations in SLC were transfected into barley protoplasts, and the requirements for minus- and plus-strand replication were found to correlate well with the requirements in vitro. Furthermore, previous analysis of replicase recognition of the Cucumber mosaic virus (CMV) and BMV SLCs indicates that the requirements in the BMV SLC are highly specific. In protoplasts, we found that BMV RNA3s with their SLCs replaced with two different CMV SLCs were defective for replication. In vitro results generated with the BMV replicase and minimal-length RNAs generally agreed with those of in vivo BMV RNA replication. To extend this conclusion, we determined that, corresponding with the process of infection, the BMV replicases extracted from plants at different times after infection have different levels of recognition of the minimal promoters for plus- and minus-strand RNA syntheses.